Ball-milling effects on the charging of lithium-oxygen battery - Kang, Yi Hao. (2013)
Lithium-Oxygen batteries are considered as one of the future battery technology due to their high theoretical energy-density potential. The theoretical specific energy of Lithium-Oxygen battery is around 11.5Wh/kg. This is due to light weight anode and the expectation that oxygen can be obtained from the atmosphere. The chemistry of Lithium-Oxygen battery in a non-aqueous system involves the electro-deposition and decomposition of Li2O2 during discharge and charging respectively. Among the numerous challenges of this system is the high charging over-potential that limits energy efficiency and cycling performance. The focus of this work is to investigate the effects of structural variation of the Li2O2 to the charging performance. Investigations are conducted with ball-milling the commercial Li2O2 and mixing it with graphitized carbon black and PVDF binder in the glove-box to assemble the cathode. With increasing structural disorder of the Li2O2 particles, the charging performance of Lithium-Oxygen battery is modified with respect to charging capacity. Studies on the charging of Lithium-Oxygen battery have shown observable trend with decrease in charging capacity shown in the Cyclic-Voltammetry (CV) with increase in ball-milling duration on the Li2O2 particles. In addition, XRD, FESEM and Raman Spectroscopy have been conducted to aid the study of particle size, defects and components present in carbon cathode.